Anaerobic co-digestions of agro-industrial waste blends using mixture design. (March 2019) - Rahman, Md Anisur; Saha, Chayan Kumer; Ward, Alastair James; Møller, Henrik Bjarne; Alam, Md Monjurul
Abstract: Batch assays were performed under a stressed condition during the anaerobic digestion process to assess the effect of component proportions on the quantity and pattern of biochemical methane yield of two sets of mixtures, consisting of poultry droppings (PD) with sugarcane bagasse (SB) and press mud (PM) for set A and PD with sugar beet roots and tops (SBRT) and PM for set B. Augmented simplex centroid design was used to design the mixture composition for the anaerobic co digestion. The reactor performances were assessed under identical conditions using cumulative methane yield (CMY) and percentage volatile solids destruction (PVSD) as the criteria. The maximum volume of methane were obtained 48.5 NL CH4 kg −1 VS at mixture proportion of 66.67% of PM, 16.665% of PD and 16.665% of SB for set A and 44 NL CH4 kg −1 VS at mixture proportion of 50% of PM and 50% of PD for set B. Synergistic effect were observed by adding a greater proportion of PM for both the sets of A and B. Antagonistic effect were obtained by adding a greater proportion of SB for set A and a higher proportion of SBRT for set B. Response surface methods and modeling were used to find out optimum mixture combinations for maximizing the methane production. From the optimization plots, the use of PD having the antagonistic effect was found for both the sets of A and set B. Graphical abstract: Image 1 Highlights: Batch assays using mixture design were conducted under stressed conditions. Study was performed to assess the effect of component proportions on methane yield. The highest (48.5 NL) CH4 kg −1 VS was found at 67% (PM) + 17% (PD) + 16% (SB) -(set A). The highest (44 NL) CH4 kg −1 VS was found at 50% (PM) and 50% (PD) -(set B). Synergistic effect was observed by adding a greater portion of PM for both the sets.